Efficacy and safety of nab-paclitaxel 125 mg/m2 and nab-paclitaxel 150 mg/m2 compared to paclitaxel in early high-risk breast cancer: results from the neoadjuvant randomized GeparSepto study (GBG 69) - Furlanetto, Jenny; Jackisch, Christian; Untch, Michael; Schneeweiss, Andreas; Schmatloch, Sabine; Aktaş, Bahriye; Denkert, Carsten; Wiebringhaus, Hermann; Kümmel, Sherko; Warm, Mathias; Paepke, Stefan; Just, Marianne; et al. (Breast cancer research and treatment, 2017)
Purpose: The GeparSepto study demonstrated that the use of nab-paclitaxel instead of paclitaxel prior to anthracycline-based chemotherapy could lead to a significantly increased pCR rate, especially in the triple negative subpopulation. We report efficacy and safety for patients treated with two different doses of nab-paclitaxel in comparison to weekly solvent-formulated paclitaxel.MethodsPatients were treated for 12 weeks with either intravenous nab-paclitaxel 150 mg/m2 (nP150) weekly, after study amendment 125 mg/m2 (nP125) weekly or solvent-based paclitaxel 80 mg/m2 (P80) weekly followed by epirubicin 90 mg/m2 and cyclophosphamide 600 mg/m2 on day 1 for four 3-week cycles.Results229 patients received nP150, 377 nP125. Baseline characteristics were fairly balanced between these two sequential cohorts as well as compared to 601 patients receiving P80 except for hormone receptor status, HER2 status, and Ki67. Taxane treatment was discontinued in 26.8% (nP150), 16.6% (nP125), and 13.3% of (P80) patients, respectively. Median relative total dose intensity (mRTDI) based on 125 mg/m2 for nP was 103% with nP150, 95% with nP125, 99% with P80 before and 98% with P80 after the amendment. PSN grade 3-4 was observed in 14.5% of patients with nP150, 8.1% of patients with nP125 (p = 0.018), and 2.7% of patients with P80. Overall pCR before the amendment was 33.6% after nP150 and 23.5% after P80 (OR 1.65 [95% CI 1.10-2.50]; p = 0.022); pCR after the amendment was 41.4% after nP125, and 32.4% after P80 (1.48 [95% CI 1.10-1.99]; p = 0.013).ConclusionsNab-paclitaxel 125 mg/m2 was associated with a better safety profile and compliance without compromising the efficacy compared to nab-paclitaxel 150 mg/m2.
Im Titel ist die Zahl "2" bei m2 hochgestellt